Mitochondrial morphology in fertile and infertile men: image processing and morphometric analysis of the sperm midpiece - Skowronek, María Fernanda; Pietroroia, Santiago; de Cola, Gabriel; Ramos, Mauricio; Silvera, Diego; Casanova, Gabriela; Lecumberry, Federico; Cassina, Adriana; Sapiro, Rossana (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe male factor is responsible for 50% of infertility cases. Numerous studies have explored the relationship between human sperm morphology assessed via optical and electron microscopy and reproductive outcomes. In the sperm midpiece, mitochondria are arranged in a helical shape, forming a compact sheath. Disruptions in this precise mitochondrial structure, size, or organization may contribute to infertility. However, despite established links between abnormal sperm morphology and pathology, mitochondrial abnormalities in sperm remain relatively understudied.MethodsIn this study, we employed computational image analysis and fluorescence labelling to quantitatively assess morphometric changes in the sperm midpiece and correlate these findings with mitochondrial ultrastructure in fertile and infertile men.ResultsOur results revealed a significant increase in midpiece area, width, and roundness in sperm from men with teratozoospermia. These findings were further validated by electron microscopy. The ultrastructural morphometric analysis demonstrated disassembled, enlarged, and irregularly shaped mitochondria in sperm from infertile men. Additionally, we applied ultrastructural morphometric analyses to apoptotic sperm samples, observing similar qualitative and quantitative mitochondrial alterations, particularly in those from infertile individuals.DiscussionTraditional sperm morphology assessments are inherently subjective, but this limitation can be addressed through quantitative morphometric analysis. Enhancing the objectivity and precision of such evaluations is essential for elucidating the biological mechanisms of male infertility and optimizing assisted reproductive technologies. In our study, spermatozoa with poor morphology (<4%) and proximal flagellar abnormalities displayed significantly shorter and wider midpieces. Ultrastructural analysis further revealed that mitochondria in sperm from infertile men were significantly larger and more irregular in shape compared to those from fertile men. These findings indicate an association between altered midpiece morphometry, mitochondrial ultrastructure, and male infertility. The integration of computational tools for automated detection and quantification of these morphological changes offers a promising avenue to improve diagnostic accuracy and deepen our understanding of male reproductive disorders.